Measures of sustainable construction projects performance - Oke, Ayodeji E. (Emerald Publishing Limited, 2022)
The construction industry contributes to growth and economic development in countries around the world, but it can also be wasteful and environmentally damaging. Traditionally, the success of construction projects is measured in term of time, cost, and quality; however, due to changing clients' demands and expectations and complexity of projects, project goals are no longer limited to the conventional three indicators. The introduction of sustainability principle in every sector of the economy, especially through the United Nations Sustainable Development Goals (UNSDGs), has also affected the measures of project success. There is the need for construction projects to adopt sustainable principles such as reduce, reuse, and recycle with a view to ensuring that projects are economical, people oriented, environmentally friendly and technically appropriate. Oke builds on years of knowledge and research providing a comprehensive discussion on various metrics and variables for measuring the success and performance of sustainable construction projects; culminating in an essential text for various stakeholders concerned with the management and administration of construction and infrastructure projects in the Architecture, Engineering, Construction and Operation (AECO) industry.